Patterns, management options and outcome of blunt thoracic aortic injuries: a 20-year experience from a Tertiary Care Hospital - Hassan Al-Thani (440106) (2022)
Background Blunt Thoracic aortic injury (BTAI) is the second leading cause of mortality after head injuries in blunt trauma patients. There is a paucity of information on the presentation, management and outcome of BTAIs from the Middle Eastern region. We explored the patterns, management options and outcomes of BTAIs in a level I trauma center. Methods We conducted a retrospective observational study on all adult patients who were admitted with BTAIs between 2000 and 2020. Patients were compared for the management option (conservative vs endovascular aortic repair (TEVAR) vs open surgery) and outcomes. Comparison between the respective groups was performed using one-way analysis of variance for continuous variables, and Pearson chi-square test for categorical variables. Kaplan–Meier curve and Cox regression analysis were performed for the outcome. Results Eighty-seven patients had BTAI (82% male) with mean age 37.3 ± 14.5 years. The mean injury severity score was 30 ± 10 and the aortic injury grade was III (I–IV). Grade III (41.4%) and Grade IV (33.3%) injuries were more common followed by Grade II (13.8%) and Grade I (11.5%). Forty percent of cases were treated conservatively whereas aortic interventions were performed in 60% of cases (n = 52). The TEVAR was performed in 33 patients (63.5%), and 19 (36.5%) were treated with open surgery (14 with graft interposition and 5 with clamp and direct repair). The aortic injury grade was significantly higher in the intervention groups as compared to the conservative group (p = 0.001). Patients with Grade IV injuries were more likely to be treated by open repair whereas a higher frequency of patients with grade III was managed by TEVAR (p = 0.001). All the patients with Grade I–II were treated conservatively. The overall in-hospital mortality rate was 25.3% and it was significantly higher in the conservative group (40.0%) in comparison to the open repair (31.6%) and TEVAR (6.1%) group (P = 0.004). More of the non-survivors sustained head injuries (P = 0.004), had higher ISS (P = 0.001) and greater aortic injury grades (P = 0.002), and were treated non-operatively (P = 0.001). Conclusions BTAI seems not common in trauma, however, one quarter of cases died in a level 1 trauma center, prehospital deaths were not analyzed, and postmortem examination was lacking. The associated head injury and aortic injury grade have an impact on the management option and hospital outcome. The conservative and TEVAR options were performed almost equally in 78% of cases. TEVAR and open surgery were performed only for aortic injury grade III or IV whereas the conservative treatment was offered for selected cases among the 4 injury grades. However, the mortality was higher in the conservative followed by the open surgery group and mostly due to the associated severe head injury. TEVAR should be considered for patients requiring intervention unless contraindicated due to technical difficulties. Appropriately selected patients with low-grade injuries may be managed conservatively. Long-term follow-up is needed in young adults for concerns of aortic remodeling and complications. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00068-022-01930-1